Structural analysis of P. falciparum KAHRP and PfEMP1 complexes with host erythrocyte spectrin suggests a model for cytoadherent knob protrusions. - Erin E Cutts; Niklas Laasch; Dirk M Reiter; Raphael Trenker; Leanne M Slater; Phillip J Stansfeld; Ioannis Vakonakis (PLoS Pathogens)
Plasmodium falciparum Erythrocyte Membrane Protein 1 (PfEMP1) and Knob-associated Histidine-rich Protein (KAHRP) are directly linked to malaria pathology. PfEMP1 and KAHRP cluster on protrusions (knobs) on the P. falciparum-infected erythrocyte surface and enable pathogenic cytoadherence of infected erythrocytes to the host microvasculature, leading to restricted blood flow, oxygen deprivation and damage of tissues. Here we characterize the interactions of PfEMP1 and KAHRP with host erythrocyte spectrin using biophysical, structural and computational approaches. These interactions assist knob formation and, thus, promote cytoadherence. We show that the folded core of the PfEMP1 cytosolic domain interacts broadly with erythrocyte spectrin but shows weak, residue-specific preference for domain 17 of α spectrin, which is proximal to the erythrocyte cytoskeletal junction. In contrast, a protein sequence repeat region in KAHRP preferentially associates with domains 10-14 of β spectrin, proximal to the spectrin-ankyrin complex. Structural models of PfEMP1 and KAHRP with spectrin combined with previous microscopy and protein interaction data suggest a model for knob architecture.